The Milk of the Male Species from legislative perspective and Rules (Islamic Sciences Journal, 2023)
Breast feeding in the linguistic term is the name of breast sucking and drinking milk. Terminologically it is the sucking of a special person, from a special breast at a fixed time. Scholars differ in the rule of the spread of the sanctity with the milk of a male (Al-fahal) born to the woman from her husband and she breastfed him a child, he becomes a son of breastfeeding for her husband, and is forbidden to him, to his origins and branches, brothers, sisters, uncles and aunts. Some scholars adopt this opinion, and went part of the other to that the child becomes a son of breastfeeding, and is forbidden to her and her origins, relatives, brothers, sisters, uncles and aunts, and prohibition does not spread to her husband.The husband may leave his wife as a result of divorce or death and he has milk, so she marries another man who is one of five conditions, and the jurists agreed on three of them and disagreed on the remaining two.The jurists differ in the ruling on the spread of the sanctity with milk generated for no legitimate reason, such as the birth of milk in women because of prolific tend , and the infant was given to him by a small human being, the first of which is: "The sanctity is spread by the milk of male produced by adultery, and the second is spread by the inviolable milk generated by adultery.
Keywords: Laban , Al-fahl , Father ، Because